Event‐triggered control of singularly perturbed linear system with DoS attacks - Xiang Ren; Fei Hao (IET Control Theory & Applications, 2021)
Abstract This paper presents the event‐triggered control problem of linear singularly perturbed systems in the presence of denial‐of‐service attacks. To save the communication and computing resources, event‐triggered mechanisms in two transmission channels are used to guarantee the ultimately bounded stability of the closed‐loop system. Absolute event‐triggering conditions are proposed in the sensor and the controller nodes, where the controller node utilises only the state of the slow model of the singularly perturbed system. Positive lower bounds of inter‐event times are given to eliminate Zeno behaviour in the presence and absence of DoS attacks. Finally, two examples are provided to illustrate the efficiency and feasibility of the obtained results.